Semiconductor gas sensors for air pollution control - Zhu, Weiguang. (2008)
In this thesis, the ferroelectric thin films of barium strontium titanate (BST) and lead zirconate titanate (PZT as the sandwiched film integrated within the Pd/ferroelectric/Pt heterostructures for hydrogen gas sensing application have been symstematically investigated.